Cultural and Artistic Differences in The Staging Process in Uzbek, Russian And English Theatres - Xayitbayeva Madinaxon Ismoiljon qizi (International Journal Of Literature And Languages, 2026)
The staging of theatrical performances reflects the cultural, historical, and aesthetic traditions of a society. This article analyzes the distinctive features of staging practices in Uzbek, Russian, and English theatres through a comparative methodological approach. Particular attention is given to cultural foundations, actor training traditions, directing methods, and technical stage design. Uzbek theatre is characterized by a strong connection to national cultural heritage, ethnographic elements, and emotional realism. Russian theatre emphasizes psychological depth and systematic actor training, largely influenced by the Stanislavski system and other methodological schools. English theatre combines classical dramaturgical traditions with contemporary stage technologies and experimental visual aesthetics. The study demonstrates that although these theatrical traditions share common artistic principles, they differ significantly in their staging strategies, technological integration, and conceptual directing approaches. These differences reflect their historical development and cultural contexts while contributing to the diversity and evolution of contemporary global theatre practices.